INCLUSIVE STRATEGIES TO ADDRESS LANGUAGE ABILITY DISPARITIES IN EARLY CHILDHOOD AT TK MARSUDI RINI, KARANGANYAR SUB- DISTRICT, DEMAK REGENCY - Najichah, Amalia Fajriyyatin Najichah (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to identify language disparities in early childhood and inclusive education strategies in Marsudi Rini Kindergarten, Karanganyar District, Demak Regency. Using a case study method with a qualitative descriptive approach, data was collected through observation, interviews, questionnaires, and documentation. The results of the study showed that childrenwith language limitations faced difficulties in speaking, understanding instructions, reading and writing skills, and social interaction. However, an intensive approach is not carried out by all teachers who have children with language disparities in their classrooms. Furthermore, the main obstacles in the implementation of inclusive education include limited facilities, lack of teacher training, low parental understanding, and lack of external support from the government. This study underscores the importance of training for teachers and improving facilities to be able to overcome disparities in children's language skills more effectively. Parent education through parentingactivities is expected to increase understandingand involvement in child development. In addition, external support is needed for the sustainability of inclusive programs in schools.